1992
DOI: 10.1039/c39920001120
|View full text |Cite
|
Sign up to set email alerts
|

Indirect electroreductive radical cyclization of halogeno ethers using nickel(II) complexes as electron-transfer catalysts

Abstract: Indirect electrochemical radical cyclization of halogeno ethers is achieved under mild conditions using nickel(i1) complexes as electron-transfer catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…Subsequent investigations of processes catalyzed by nickel(I) tetraazamacrocyclic complexes were carried out by Bakac, Espenson, and Ram [6][7][8][9][10]14,15], and Stolzenberg and co-workers probed nickel(I) hydroporphyrin-catalyzed reductions of alkyl halides [11][12][13]17,20]. A number of interesting reductive cyclizations of halogenated compounds promoted by electrogenerated nickel(I) species have been reported by Ozaki and co-workers [16,19,22,23,[25][26][27][28] and by Duñ ach et al [24,[29][30][31]33,35,[37][38][39][40]. Additional papers have appeared from the laboratories of Helvenston and Castro [18], Fry and Fry [21], Esteves and co-workers [32], and Gennaro and Isse [34,36].…”
Section: Introductionmentioning
confidence: 94%
“…Subsequent investigations of processes catalyzed by nickel(I) tetraazamacrocyclic complexes were carried out by Bakac, Espenson, and Ram [6][7][8][9][10]14,15], and Stolzenberg and co-workers probed nickel(I) hydroporphyrin-catalyzed reductions of alkyl halides [11][12][13]17,20]. A number of interesting reductive cyclizations of halogenated compounds promoted by electrogenerated nickel(I) species have been reported by Ozaki and co-workers [16,19,22,23,[25][26][27][28] and by Duñ ach et al [24,[29][30][31]33,35,[37][38][39][40]. Additional papers have appeared from the laboratories of Helvenston and Castro [18], Fry and Fry [21], Esteves and co-workers [32], and Gennaro and Isse [34,36].…”
Section: Introductionmentioning
confidence: 94%
“…The formation of dimer 12 was also observed and identified by Ozaki et al [39] and Olivero et al [1] in the study of indirect electroreductive radical cyclisations of halogeno ethers using nickel(II) complexes as electrontransfer catalysts. Moreover, Olivero et al [1] also reported the cyclisation of 4 in the presence of [Ni(cyclam)]Br 2 in DMF; using controlled-potential electrolysis they found that the reduction was catalytic in nickel giving rise to the formation of 8 in 62% yield along with dimer 12 and the debromination product, allyl phenyl ether 10.…”
Section: Ni-c Bond and Hence Is Insufficiently Influenced By The Chirmentioning
confidence: 72%
“…[188] Electrochemical cyclisation of unsaturated 2-bromo ethers has been achieved under mild conditions using macrocyclic Ni II complexes as catalysts; diphenyltetrahydrofuran was prepared in 85% yield. [189] A tandem radical-mediated fragmentation of 2,3-epoxy bromides to form cyclopentanols and cis-fused bicyclic compounds in yields of up to 58% has been reported in a [Ni(tmc)](ClO 4 ) 2 -catalysed electroreduction in DMF (Scheme 43). [190] The reaction was proposed to proceed through the formation and rearrangement of alkyloxy radicals.…”
Section: ) Reductive Coupling Of Organic Halides With C؊c Double or mentioning
confidence: 99%